X-ray stability and response of polymeric photodiodes for imaging applications - Keivanidis, Panagiotis E.; Greenham, Neil C.; Sirringhaus, Henning; Friend, Richard H.; Blakesley, James C.; Speller, Robert; Campoy-Quiles, Mariano; Agostinelli, Tiziano; Bradley, Donal D.C.; Nelson, Jenny (My University, 2008)
The x-ray stability of photodiodes made of poly(9,9-di- n -octylfluorene-co-benzothiadiazole):perylene diimide, poly[2,7-(9,9-di- n -octylfluorene)-co-(1,4-phenylene-[(4-sec-butylphenyl)imino]-1,4-phenylene)]: perylene diimide and poly(3-hexylthiophene):([6,6]-phenylC61-butyric acid methyl ester) (P3HT:PCBM) blends has been examined up to lifetime doses equivalent to those used in medical x-ray digital imaging applications. Dark currents and external quantum efficiencies (EQEs) are not significantly affected after exposure to 500 Gy. Only in the case of P3HT:PCBM is a significant loss in EQE (17% of the initial value) observed. Possible reasons for the observed changes are proposed. When a scintillation layer is attached to the devices, a linear dependence of the photocurrent on the x-ray dose rate is observed for the three material systems. © 2008 American Institute of Physics.